Detection of a deep-water channel in 3D seismic data using the sweetness attribute and seismic geomorphology: a case study from the Taranaki Basin, New Zealand. Issue 3 (3rd July 2017) - Li, Quan; Yu, Shui; Wu, Wei; Tong, Liqing; Kang, Hongquan
ABSTRACT: In recent years, the three-dimensional seismic method has become an essential tool for the interpretation of subsurface stratigraphy and depositional systems. Seismic stratigraphy, in conjunction with seismic geomorphology, has elevated the degree to which seismic data can facilitate geological interpretation, especially in deep-water environments. Techniques such as time slicing and interval attribute analysis can enhance geomorphological interpretations and, when integrated with stratigraphic analyses, can yield insights regarding the distribution of seal and reservoir facies. Sweetness is a seismic attribute that can be very useful for channel detection in deep-water clastic settings, especially when used in conjunction with coherency in plan view. In this article, we present an example of a deep-water channel complex from a three-dimensional seismic volume that is derived using co-rendered sweetness and semblance attributes. The advantages of and workflow followed for the co-rendered attributes are discussed. The application of this technique to a dataset in the offshore Taranaki Basin, New Zealand, has led to the observation of four channel elements: (1) point-bars, (2) the migration of channel meander loops, (3) channel erosion and cutting, and (4) avulsion. This technique enables the detailed visualisation of complex depositional elements, and could be used to predict sands in the channel systems, which is of vital importance for evaluating the distribution of deep-water sandstone reservoirs. The technique is applied to the study area in an effort to illustrate the variety of interpretation techniques available to the geoscientist.